Environmental source, fate, and toxicity of microplastics - Wang, Chunhui; Zhao, Jian; Xing, Baoshan (Journal of hazardous materials, 2021)
Microplastics are small plastic pieces with sizes less than 5 mm. Due to their widespread distribution in different environmental compartments, food, and drinking water, microplastics have attracted increasing attention across the world. Previous reports have focused on the source, distribution, fate, and toxicity of microplastics. However, many of these studies and reviews are not quite comprehensive, and most of them have only focused on marine environments. Therefore, we comprehensively reviewed the available literature on the source, occurrence, and fate of microplastics in different environments, including air, freshwater, soil, and ocean, across the world. Our review suggests that the sources of microplastics are extensive and diverse and that their occurrence, transport, and fate in the environment are affected by a variety of natural factors as well as their own physicochemical properties. Studies on the toxicological effects of microplastics are also reviewed. We found that large research gaps exist in the quantitative analysis of different exposure routes of microplastics, and microplastic toxicity to organisms. Moreover, key suggestions for future research are presented, and we call for more efforts focusing on the occurrence and fate of microplastics in terrestrial environments, especially in the atmosphere and soil, and further investigations on the toxicity mechanisms of microplastics. [Display omitted] •The sources, occurrence, and fate of environmental microplastics (MPs) are reviewed.•MPs are widely distributed in different environmental compartments.•Natural factors and physicochemical property of MPs influence their distributions.•Human exposure and toxicological effects of MPs are presented.•Possible risks of MPs to human health are discussed.